Book Reviews - Salevouris, Michael J.; Brown, Robert W.; Frey, Linda; Lindsay, Robert; Larson, Arthur Q.; Allen, Calvin H.; Dicks, Samuel E.; Boland, Brian; Arbena, Joseph L.; Nass, David L.; et al. (Teaching History: A Journal of Methods, 1987)
Eliot Wigginton. Sometimes a Shining Moment: The Foxfire Experience– Twenty Years in a High School Classroom. Garden City, New York: Anchor Press/ Doubleday, 1985. Pp. xiv, 438. Cloth, 19.95. Review by Philip Reed Rulon of Northern Arizona University. Eugene Kuzirian and Larry Madaras, eds. Taking Sides: Clashing Views on Controversial Issues in American History. Vol. I: The Colonial Period to Reconstruction. Guilford , Connecticut: Dushkin Publishing Group, Inc., 1985. Pp. x, 255. Paper, 8.95. Review by Jayme A. Sokolow of the National Endowment for the Humanities. Lois W. Banner. American Beauty. Chicago and London: University of Chicago Press, 1983. Pp. ix, 369. Paper, 9.95. Review by Thomas J. Schlereth of the University of Notre Dame. Alan Heimert and Andrew Delbanco, eds. The Puritans in America: A Narrative Anthology. Cambridge: Harvard University Press, 1985. Pp. xviii, 438. Cloth, 25.00. Review by Raymond C. Bailey of Northern Virginia Community College. Clarence L. Mohr. On the Threshold of Freedom: Masters and Slaves in Civil War Georgia. Athens and London: The University of Georgia Press, 1986. Pp. xxi, 397. Cloth, 35.00. Review by Charles T. Banner-Haley of the Frederick Douglass Institute for African and African-American Studies, University of Rochester. Francis Paul Prucha. The Indians in American Society: From the Revolutionary War to the Present. Berkeley: University of California Press, 1985. Pp. ix, 127. Cloth, 15.95. Review by Darlene E. Fisher of New Trier Township High School, Winnetka, Il. Barry D. Karl. The Uneasy State: The United States from 1915 to 1945. Chicago and London: University of Chicago Press, 1983. Pp. x, 257. Paper, 7.95; Robert D. Marcus and David Burner, eds. America Since 1945. New York: St. Martin’s Press, 1985. Fourth edition. Pp. viii, 408. Paper, 11.95. Review by David L. Nass of Southwest State University, Mn. Michael P. Sullivan. The Vietnam War: A Study in the Making of American Policy. Lexington: The University Press of Kentucky, 1985. Pp. 198. Cloth, 20.00. Review by Joseph L. Arbena of Clemson University. N. Ray Hiner and Joseph M. Hawes, eds. Growing Up In America: Children in Historical Perspective. Urbana and Chicago: University of Illinois Press, 1985. Pp. xxv, 310. Cloth, 27.50; Paper, 9.95. Review by Brian Boland of Lockport Central High School, Lockport, IL. Linda A. Pollock. Forgotten Children: Parent-Child Relations from 1500 to 1900. Cambridge: Cambridge University Press, 1983. Pp. xi, 334. Cloth, 49.50; Paper, 16.95. Review by Samuel E. Dicks of Emporia State University. Yahya Armajani and Thomas M. Ricks. Middle East: Past and Present. Englewood Cliffs, New Jersey: Prentice-Hall, Inc., 1986. Second edition. Pp. xiv, 466. Cloth, 16.95. Review by Calvin H. Allen, Jr of The School of the Ozarks. Henry C. Boren. The Ancient World: An Historical Perspective. Englewood Cliffs, New Jersey: Prentice-Hall, Inc., 1986. Pp. xx, 407. Paper, 22.95. Review by Arthur Q. Larson of Westmar College (Ret.) Geoffrey Treasure. The Making of Modern Europe, 1648-1780. London and New York: Methuen, 1985. Pp. xvii, 647. Cloth, 35.00; Paper, 16.95. Review by Robert Lindsay of the University of Montana. Alexander Rudhart. Twentieth Century Europe. Englewood Cliffs, New Jersey: Prentice-Hall, Inc., 1986. Pp. xiv, 462. Paper, 22.95. Review by Linda Frey of the University of Montana. Jonathan Powis. Aristocracy. New York: Basil Blackwell, 1984. Pp. ix, 110. Cloth, 24.95; Paper, 8.95. Review by Robert W. Brown of Pembroke State University. A. J. Youngson. The Prince and the Pretender: A Study in the Writing of History. Dover, New Hampshire: Croom Helm, Ltd., 1985. Pp. 270. Cloth, 29.00. Review Michael J. Salevouris of Webster University.